1998 Annual Report Conference on Electrical Insulation and Dielectric Phenomena (Cat. No.98CH36257)
DOI: 10.1109/ceidp.1998.732949
|View full text |Cite
|
Sign up to set email alerts
|

Straight through cold-applied shrinkable EPDM cable joints designed for high stress medium voltage EPR cables

Abstract: The introduction of high electrical stress EPR insulated medium voltage cables leads to the development of new cable joints suitable for installation. This paper presents the joint design considerations and test data. The test program is based on IEEE Standard 404-1993. Test samples include joints for high stress EPR cables and transition joints from high stress EPR cables to PILC cables. All test results have shown that both joint designs comply with the IEEE standard and suitable for operation in cable netwo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Further research [22] has indicated a need for a third variable in determining the minimum allowable insulation thickness. While this third variable is still related to voltage stress, it relates to the voltage stress at the insulation/insulation-shield interface.…”
Section: Design and Constructionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Further research [22] has indicated a need for a third variable in determining the minimum allowable insulation thickness. While this third variable is still related to voltage stress, it relates to the voltage stress at the insulation/insulation-shield interface.…”
Section: Design and Constructionsmentioning
confidence: 99%
“…The voltage stress at the conductor-shield/insulation is important to the capabilities of the insulation itself, but the stress at the insulation/insulation-shield interface is vital to the X THE 15-kV CLASS EPR INSULATION THICKNESS TABLE XI THE 25-kV CLASS EPR INSULATION THICKNESS TABLE XII THE 35-kV CLASS EPR INSULATION THICKNESS capabilities of the accessories that may be used in conjunction with the cable. The voltage stress limit at the insulation/insulation-shield interface based on this research [22] was established as a maximum of 2.4 kV/mm (61 V/mil). This value was determined based on positive test results on a 750-kcm, 3.18-mm (125-mil) cable.…”
Section: Design and Constructionsmentioning
confidence: 99%
See 1 more Smart Citation